Exploring the Regulatory Function of the N‐terminal Domain of SARS‐CoV‐2 Spike Protein through Molecular Dynamics Simulation (Adv. Theory Simul. 10/2021). Issue 10 (4th October 2021) - Li, Yao; Wang, Tong; Zhang, Juanrong; Shao, Bin; Gong, Haipeng; Wang, Yusong; He, Xinheng; Liu, Siyuan; Liu, Tie‐Yan
Abstract : N ‐terminal Domain of SARS‐CoV‐2 Spike Protein In article number 2100152, Yao Li, Tong Wang, Haipeng Gong, and co‐workers propose the "wedge" model to demonstrate the regulatory function of the N ‐terminal domain (NTD) of SARS‐CoV‐2 Spike protein. The NTD typically wedges in to prohibit receptor binding domain's (RBD's) movements and it occasionally moves out to allow RBD to tilt downward.